2004
DOI: 10.1007/s00464-004-9000-0
|View full text |Cite
|
Sign up to set email alerts
|

The optimal mechanical efficiency of laparoscopic forceps

Abstract: The optimal mechanical efficiency of laparoscopic forceps is dependent on the task that is performed. For tasks requiring little movement of the forceps, such as grasping and holding tissue, a low mechanical efficiency is sufficient, whereas for tasks requiring repeated movement of the forceps to feel tissue, a high mechanical efficiency is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…These values are averages calculated for grasps maintained for 4 s. The results of the measurement of the grasping force achieved using the handpiece are shown in Figure 7. A previous study concluded that the pinch force necessary to avoid slippage is more than 3.3 N [12]. Because the forceps was able to produce grasping forces of more than 3.3 N with both the motor drive and the handpiece, we conclude that the forceps produces sufficient grasping force for it to be used in practical applications.…”
Section: Results Of Grasping Force Measurement Experimentsmentioning
confidence: 59%
“…These values are averages calculated for grasps maintained for 4 s. The results of the measurement of the grasping force achieved using the handpiece are shown in Figure 7. A previous study concluded that the pinch force necessary to avoid slippage is more than 3.3 N [12]. Because the forceps was able to produce grasping forces of more than 3.3 N with both the motor drive and the handpiece, we conclude that the forceps produces sufficient grasping force for it to be used in practical applications.…”
Section: Results Of Grasping Force Measurement Experimentsmentioning
confidence: 59%
“…For the offset-bending manipulator, the positional accuracy was also 0.5 mm from the forceps tip trajectory measurements. When the organ was pulled up by the manipulator, the traction force has to exceed 5 N [19]. It was con rmed that the offset angle was maintained to pull up the model organ because of the allowance for wire tension force based on the experimental results.…”
Section: Discussionmentioning
confidence: 98%
“…Based on these results, further improvements are being planned to develop the offset-bending manipulator for clinical use. First, the grasp and traction force must exceed 5 N [19], and the friction resistance of the transmission mechanisms should be lower. Second, an intuitive interface with 5 DOFs is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Heijnsdijk et al [22] evaluated the effects from differences in the force transmission ratios of laparoscopic forceps and concluded that the efficiency is dependent on the task being performed. Whereas a low force transmission ratio is sufficient for tasks requiring little movement of the forceps, such as grasping and holding tissue, a high force transmission ratio is required for tasks requiring repeated movement of the forceps.…”
Section: Discussionmentioning
confidence: 99%